6+1 Writing Traits in a Matriculation ESL classroom - GURUSAMY, Premaraj; Sathappan, Ramesh (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2022)
The purpose of this study is to examine the use of the 6+1 Writing Traits approach in improving teaching and learning of writing in a Matriculation ESL classroom. This is due to the fact writing instruction has become a field of increasing interest at higher learning institutions and at pre- university levels in recent years. As a result of this interest, there have been many innovations to the teaching of writing in the evolution of language teaching and these have led to several significant shifts on how writing is taught in the ESL classrooms. The 6+1 writing traits is one such innovation. Writing traits such as Ideas, Organization, Convention, Sentence Fluency, Word Choice and Voice are important in any writing attempted by learners. Therefore, it is vital that Matriculation learners are exposed to the 6+1 writing traits in order to be able to produce a comprehensive essay that meets the requirements of the Malaysian University English Test examination. This proposed research will be a qualitative research. Pre-test, lessons plans, classroom observations, questionnaire and post-test will be used to elicit data in support of this research. Learners will learn to review peer essays thus enhancing their writing proficiency. This research will also look into the challenges faced by learners and lecturers in the course of implementing the 6+1 writing traits in the classroom.